Physical Metallurgy of High Manganese Steels - Bleck, Wolfgang (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The Special Issue 'Physical Metallurgy of High Manganese Steels' addresses the highly fascinating class of manganese-alloyed steels with manganese contents well above 3 mass%. The book gathers manuscripts from internationally recognized researchers with stimulating new ideas and original results. It consists of fifteen original research papers. Seven contributions focus on steels with manganese contents above 12 mass%. These contributions cover fundamental aspects of process-microstrcuture-properties relationships with processes ranging from cold and warm rolling over deep rolling to heat treatment. Novel findings regarding the fatigue and fracture behavior, deformation mechanisms, and computer-aided design are presented. Additionally, the Special Issue also reflects the current trend of reduced Mn content (3-12 mass%) in advanced high strength steels (AHSS). Eight contributions were dedicated to these alloys, which are often referred to as 3rd generation AHSS, medium manganese steels or quenching and partitioning (Q&P/Q+P) steels. The interplay between advanced processing, mainly novel annealing variants, and microstructure evolution has been addressed using computational and experimental approaches. A deeper understanding of strain-rate sensitivity, hydrogen embrittlement, phase transformations, and the consequences for the materials' properties has been developed. Hence, the topics included are manifold, fundamental-science oriented and, at the same time, relevant to industrial application.